Influence of Growth Regulators on Seed Germination and Seedling Vigour in West Himalayan Banj Oak (Quercus leucotrichophora A. Camus) - BIRENDRA PRASAD; RAJENDRA PRASAD (Seed Research, 2026)
Studies were conducted to evaluate the effect of plant growth regulators on seed germination and seedling vigour in West Himalayan banj oak (Quercus leucotrichophora A. Camus). The results showed that all treatments have significantly higher germination and seedling vigour over control. Among different treatments, seeds were soaked for 24h in GA, Ethanol, IAA 100mg 1¹ and 1BA 200 mg 1¹ performed moderate, while NAA of 100 and 200 mg I both depicted some what lower performance with respect to germination and most of the vigour test.